Merkel cell mechanotransduction facilitates adult neurogenesis and cognition in an enriched environment - Xing Luo; Qiang Liu; Dezhe Qin; Min Wang; Weixiang Guo (Proceedings of the National Academy of Sciences, 2025)
The tactile system empowers us to act on and interact with the changes of the external environment. In rodents, tactile sensation, a fundamental sense, is largely mediated via the vibrissae and the barrel cortex. However, it remains unclear how tactile perception reshape the brain when exploring a novel environment. Here, we showed that exposure to an enriched environment (EE) failed to enhance adult neurogenesis and cognition in the mice with defective touch perception due to loss of a mechanotransduction channel Piezo2 in Merkel cells. Moreover, we found an EE-activated neuraxis, in which the dentate gyrus received tactile input through a circuit that originated from the somatosensory cortex (S1) and relayed via dopaminergic neurons of the substantia nigra pars compacta (SNc). Defective touch perception diminished the S1 to SNc afferent, thereby reducing dopamine release. Notably, stimulation of the S1 to SNc afferent restored EE-induced adult neurogenesis and cognition in the mice with defective touch perception. Therefore, our study highlighted the important role of intact tactile processing in brain function.